Sanad Al-Qur’an in the Digital Era: Strategies for Improving Reading Accuracy Through Online Classes - Shobah, Fuidhatul Khoiris; Rizal, Syaiful; Istiqomah, Rofiatul (Yayasan Rahmat Islamiyah, 2025)
The purpose of this research is to thoroughly examine the implementation of online classes in learning Quranic sanad, the application of learning strategies in online classes, and the effectiveness of online learning methods in improving the accuracy of Quranic recitation. This research uses a qualitative approach with a case study type. The data in this research comes from observation activities, interviews, and documentation. The sources of information come from several informants, namely online class program contacts, teachers, students, and alumni. Additionally, the sources of information come from literature discussing topics related to the main discussion. The research results show that the implementation of online classes in learning Quranic sanad is considered effective in improving students' recitation accuracy with the use of appropriate strategies, methods, and media.